As you like it - Shakespeare, William, 1564-1616 (Staged collection., 2024)
"Banished from her ambitious uncle's court, the lovesick Rosalind flees to the forest with her cousin, Celia. Disguised as the handsome shepherd Ganymede and simple shepherdess Aliena, the two soon meet the dashing Orlando - forced into hiding by a plot against his life, heartbroken at the separation from his beloved Rosalind. Fooled by Rosalind's disguise, Orlando grows close to 'Ganymede'. But Phoebe, a local shepherdess, also has her eye on Ganymede. As their hopes and dreams entangle, can everyone get what they want?"--Amazon.com.